(untitled) (European Journal of Health Research, 2019)
Systems Training for Emotional Predictability and Problem Solving (STEPPS) is a group treatment in two phases: Basic Skills; Advanced skills in emotional and behavioral regulation for patients with BPD. This work is intended: 1) Analyze the implementation of the Basic Skills pilot group in a Mental Health Hospital 2) Identify and contrast clinical variables associated with the participants 3) Analyze results in terms of effectiveness and efficiency. 9 patients who received therapy in the different Community Mental Health Centers. Instruments: SIS, PANAS, ERQ, BDHI y PDQ-4+. Total number of assistance in mental health services before the program was 28, compared to 14 received during the treatment. 3 of 4 patients evaluated at the end of the group decreased the intensity of the desire to die and the presence of nuclear symptoms of BPD. STEPPS is an effective and efficient treatment in public mental health context. STEPPS improve emotional regulation and reduce the number of attentions in Mental Health Services.